2022
DOI: 10.1002/anbr.202200053
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Magnetic Nanoparticles for Dynamic Imaging and Therapy

Abstract: Dynamic therapy is a key research area for noninvasive clinical therapeutics. Up to now, light, electricity, ultrasound, and magnetic field have been investigated for the potential remote cellular regulation tools. Opening ion channels, activating cell death, and manipulating individual receptors that can control various cellular signal pathways have been suggested using external energy forms that can be dynamically applied in situ, which advance from the static control strategies. [1][2][3][4] For instance, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 226 publications
0
11
0
Order By: Relevance
“…An exogenous magnetic field has been widely studied in the field of biomedicine due to its highly tissue-penetrative and noninvasive characteristics. 78 Under the influence of a magnetic field, the alignment of the magnetic spin within a magnetically responsive material changes, resulting in dynamic motion (e.g., movement, vibration, rotation, etc.) that can directly influence nearby cells or release a loaded drug.…”
Section: Magnetic Field-induced Ferroptosismentioning
confidence: 99%
“…An exogenous magnetic field has been widely studied in the field of biomedicine due to its highly tissue-penetrative and noninvasive characteristics. 78 Under the influence of a magnetic field, the alignment of the magnetic spin within a magnetically responsive material changes, resulting in dynamic motion (e.g., movement, vibration, rotation, etc.) that can directly influence nearby cells or release a loaded drug.…”
Section: Magnetic Field-induced Ferroptosismentioning
confidence: 99%
“…Under alternating magnetic fields, magnetic 1-D nanomaterials efficiently produce heat that increases the local temperature due to their high responsiveness to the external magnetic field and extensive motion due to the elongated morphology. 29 Generally, magnetic hyperthermia is caused by Brownian relaxation (rotation or vibration of the particle) and Ne ´el relaxation (rotation of the internal magnetic domain), where Brownian relaxation plays a dominant role by generating frictional energy with the surroundings. 30 With their high sensitivity to the external magnetic field and extensive motion created by the elongated morphologies with a high surface-to-volume ratio, 1-D nanomaterials interact vigorously with the neighboring environment to generate a higher level of friction-mediated heat than the nanomaterials of other dimensions under the same external magnetic actuation.…”
Section: Efficient Thermal Stimulationmentioning
confidence: 99%
“…This application has been investigated extensively and determined to be highly effective in treating various target cancers under physical impact based on “mechanical force” which differs from the previous discussion of ultrasound- and magnetic-stimuli therapy that had been reported. 8–14…”
Section: Introductionmentioning
confidence: 99%
“…This application has been investigated extensively and determined to be highly effective in treating various target cancers under physical impact based on ''mechanical force'' which differs from the previous discussion of ultrasound-and magnetic-stimuli therapy that had been reported. [8][9][10][11][12][13][14] The fundamental mechanical forces are intrinsically present throughout the cellular microenvironment due to normal motion and physiological functioning of cells and sub-organelles. 15 For several decades, studies have revealed that mechanical forces drive numerous physiological processes and are a crucial regulator of cellular interaction.…”
Section: Introductionmentioning
confidence: 99%